Hyperthermia body warmer
Patent Information
- Application Number
- JP2022082519
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-05-19
- Publication Date
- 2025-01-30
AI Technical Summary
Conventional hand warmers pose risks of low-temperature burns, are uneconomical, and lack diversity, while existing heat retaining devices do not provide a warm hand warmer solution.
A thermal pocket warmer using waste-derived, natural-derived, or animal-derived materials like sodium chloride and silicate-containing components, surrounded by a flame-retardant sheet, which maintains warmth for a long time and reduces the risk of burns.
The thermal pocket warmer provides the right amount of warmth, maintains it for a long time, and is less likely to burn, while utilizing waste materials to evoke memories and give a sense of happiness.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a heated hand warmer. [Background technology]
[0002] Conventional hand warmers can be broadly classified into two types: those that utilize the heat of reaction generated by an oxidation-reduction reaction between iron powder and activated carbon via saline solution, and those that utilize far-infrared radiation by exciting the crystalline water contained in salt crystals using a microwave oven or similar device. However, the former poses the risk of low-temperature burns due to rapid chemical reactions, and particular caution is needed when used by the elderly, people with disabilities, infants, and diabetic patients. Furthermore, they are often disposable, uneconomical, waste resources, and lack variety.
[0003] A heat-retaining device has been disclosed (Patent Document 1) in which a heat-retaining material manufactured by adding glycerin, montmorillonite, calcium carbonate, and sodium chloride is wrapped in one or more films such as polyethylene, polyvinyl chloride, or polyvinyl acetate, and applied to a part of the body that emits heat to prevent heat from escaping from that part. However, this heat-retaining device uses the heat emitted by the user as a heat source and is not intended to be used as a thermal hand warmer.
[0004] A far-infrared warming system containing rock salt as a moisture-absorbing and heating substance and sand and gravel made of granular porous andesite and basalt with silicon as the main component as a far-infrared radiating substance has been disclosed (Patent Document 2). However, this far-infrared warming system uses a special sand and gravel called silica high gray and does not use waste-derived or naturally derived aluminosilicate-containing components selected from sea sand, crushed ceramics, or gemstone waste. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Public Gazette No. 61-24248 [Patent Document 2] Japanese Patent Application Publication No. 11-197175 [Non-patent literature]
[0006] [Non-Patent Document 1] United Nations Information Centre 2030 Agenda (URL: https: / / www.unic.or.jp / activities / economic_social_development / sustainable_development / 2030agenda / ) [Non-Patent Document 2] AdverTimes Column, "The True Meaning of 'From Things to Experiences' ~ What Lies Behind Experiential Branding (Part 2)" (URL: https: / / www.advertimes.com / 20180406 / article266418 / ) [Overview of the project] [Problems that the invention aims to solve]
[0007] Incidentally, unlike the era when products like those described above were proposed based on background technology, today's everyday goods require a new perspective that addresses the diverse social problems that have become apparent in recent years (SDGs; Sustainable Development Goals; Non-Patent Literature 1) and sells experiences rather than just products. Hand warmers are no exception. For example, they can be used to effectively utilize industrial waste materials, foster feelings of care and compassion for the elderly and infants, evoke memories of travel or one's hometown, or provide an opportunity to remember deceased loved ones or pets. These perspectives resonate with the feelings of those who purchase the product, evoking memories, providing healing and a moment of happiness (Non-Patent Literature 2). Without these perspectives, understanding future consumer behavior will be insufficient, and industrial development cannot be expected.
[0008] Conventional hand warmers all critically lack the attitude of addressing the diverse social problems that have become apparent in recent times, and the attitude of being attentive to people's feelings.
[0009] In view of the above circumstances, the present invention aims to provide a heated hand warmer that provides a moderate warmth that conforms to the body, maintains that warmth for a long time, and is less prone to scorching of the outer casing due to abnormal heating of the contents, and more preferably a heated hand warmer that is attuned to the user's feelings, evokes memories, provides healing, and gives a moment of happiness. [Means for solving the problem]
[0010] One aspect of the present invention, made to achieve the above objectives, is a heat pack in which a composition comprising sodium chloride and one or more waste-derived, natural, or animal-derived materials selected from waste-derived, natural, or animal-derived silicate-containing components, waste-derived or natural aluminosilicate-containing components selected from sea sand, crushed ceramics, or gemstone waste, waste-derived, natural, or animal-derived calcium carbonate-containing components, and waste-derived, natural, or animal-derived calcium phosphate-containing components is surrounded by a flame-retardant sheet. With the above configuration, by using waste-derived, natural, or animal-derived materials, the perspective of effective utilization of waste materials, the perspective of memorializing deceased people or pets, and the perspective of giving form to memories of travel or hometowns can be incorporated into the heat pack, thereby empathizing with the user's feelings, evoking memories, providing healing, and giving a moment of happiness. Furthermore, by selecting or appropriately combining one or more of the above-mentioned waste-derived, natural, or animal-derived materials, the temperature immediately after heating and the rate at which it cools down can be adjusted according to the material and thickness of the bag used for the outer covering. This makes it possible to obtain a heat pack that provides a comfortable warmth that conforms to the body and maintains that warmth for a long time, making it suitable for use at home while sleeping. In addition, by using a flame-retardant sheet, scorching and other damage are less likely to occur. In this specification, "outer covering" refers to anything that directly or indirectly surrounds the composition, and is not limited to an outer bag, but is a comprehensive term that includes non-permeable bags and permeable materials. In this specification, "surrounded" includes not only wrapping with one or more sheets, but also sandwiching with two sheets and sewing the edges together, and surrounding with three or more sheets and sewing them together.
[0011] The sheet in the above-mentioned heated hand warmer preferably contains one or more materials selected from the group consisting of polyarylate cloth, aramid cloth, polyester cloth, felt containing carbonized fibers, carbon cloth, urethane rubber sheet, silicone rubber sheet, composite material of silicone rubber sheet and hemp cloth, composite material of silicone rubber sheet and aramid fiber sheet, glass fiber sheet, glass felt, rock wool, refractory ceramic fiber sheet, AES fiber sheet, silica fiber sheet, alumina fiber sheet, and glass wool. These sheets are less likely to scorch or burn due to contact with heated coral, coral sand, etc., even after repeated use, and have high flame retardancy.
[0012] The sheet in the above-mentioned heat pack is preferably made of a layered aramid cloth and / or felt containing carbonized fibers. Aramid cloth and felt containing carbonized fibers have high heat retention, low skin irritation, and are particularly flame-retardant, making them less prone to scorching from contact with heated coral, coral sand, etc., even with repeated use. Furthermore, they are less likely to scorch even if heated at the wrong wattage, such as 1000W, or if the heating time is extended to make it warmer.
[0013] Another aspect of the present invention made to achieve the above objective is a heat pack in which a composition comprising sodium chloride and one or more waste-derived, natural, or animal-derived materials selected from waste-derived, natural, or animal-derived silicate-containing components, waste-derived or natural aluminosilicate-containing components selected from sea sand, crushed ceramics, or gemstone waste, waste-derived, natural, or animal-derived calcium carbonate-containing components, and waste-derived, natural, or animal-derived calcium phosphate-containing components is enclosed in a cotton bag or hemp bag and cotton material, hemp material, or cotton-hemp blend material, wherein the particle diameter of the waste-derived, natural, or animal-derived material is less than 2 mm. By enclosing it in a double structure of a cotton bag or hemp bag and cotton material, hemp material, or cotton-hemp blend material, heat retention is improved, and by keeping the particle diameter of the waste-derived, natural, or animal-derived material to less than 2 mm, scorching of the outer cover can be suppressed.
Advantages of the Invention
[0014] According to the present invention, by incorporating a warming hand warmer from the perspectives of effective utilization of waste materials, memorial of the deceased humans and pets, and shaping the memories of travels and hometowns, it can empathize with the user's feelings, evoke memories, soothe, and give a sense of happiness for a while. Further, according to the warming hand warmer of the present invention, the temperature immediately after heating is not too high and the heat retention property is relatively high, so that it is possible to prevent low-temperature burns and it can also be used for home use at bedtime.
Brief Description of the Drawings
[0015] [Figure 1] Deep heat dissipation graph when the ratios of coral sand, silica sand, and calcium phosphate to salt are fixed. [Figure 2] Deep heat dissipation graph when the ratio of coral sand to salt is changed. [Figure 3] Photo of a warming hand warmer made of a non-woven fabric with its four sides fused. [Figure 4] Photo of a warming hand warmer with a laminated fabric on the outside and a zipper bag on the inside. [Figure 5a] Photo of a warming hand warmer showing the fusion margin between the zipper bag and the outer bag. [Figure 5b] Inner photo of a warming hand warmer with felt sandwiched between the outer bag and the zipper bag. [Figure 5c] Inner photo of a warming hand warmer showing the cut-open laminated state of the non-water-permeable bag and the felt. [Figure 5d] Photo of a warming hand warmer showing the fusion of the zipper bag, the felt, and the outer bag. [Figure 6] Photo showing the state of a heat dissipation experiment with various compositions placed in a non-woven fabric. [Figure 7] Photo showing the measurement state of a heat dissipation experiment with various compositions placed in a beaker. [Figure 8] Front photo of a beaker with a food shelf cushion sheet wound around it four times. [Figure 9] Planar photo of a beaker with a food shelf cushion sheet wound around it four times. [Figure 10]A photograph showing an experiment in which the relationship between the surface temperature and the internal temperature of a nonwoven fabric was measured. [Figure 11] A photograph showing an experiment measuring the relationship between the deep-seated temperature of nonwoven fabric and perceived temperature. [Figure 12] A photograph showing a multi-layered heat pack containing a heat pack and coral surrounded by heat-resistant material. [Figure 13] A photograph showing each element of a multi-layered thermal hand warmer separated. [Figure 14] Coral encased in heat-resistant material. [Figure 15] A heat pack with a heat-resistant, water-permeable material surrounding the composition. [Figure 16] A photo showing the burn marks on a pinstripe towel that covered a carbon fiber heat pack. [Figure 17] A photograph of a heat pack made with patterned red laminated fabric after long-term use. [Figure 18] A photograph of a heat pack made of thin green laminated fabric after long-term use. [Figure 19] A photograph of a heated hand warmer made of navy blue laminated fabric, similar to denim, after long-term use. [Figure 20] A photograph of a small, dark blue laminated cloth hand warmer after long-term use, resembling denim. [Figure 21] A photograph of a small, dark blue laminated cloth hand warmer after long-term use, resembling denim. [Figure 22] A photo of a small pink laminated cloth hand warmer after long-term use. [Figure 23] A photograph showing an experiment in which the relationship between the surface temperature and the internal temperature of a heat pack was measured using a cotton bag or burlap bag combined with cotton material, burlap material, or a cotton-burlap blend material. [Figure 24A] Manufacturing method for a heat pack made by layering carbonized felt and aramid cloth (Part 1). [Figure 24B] The second half of the manufacturing method for a heat pack made by layering carbonized felt and aramid cloth. [Modes for carrying out the invention]
[0016] Embodiments for carrying out the present invention will be described below with reference to the drawings. The thermal hand warmer according to the present invention comprises a composition containing sodium chloride and one or more waste-derived, naturally derived, or animal-derived materials. In this specification, unless otherwise specified, the term "thermal hand warmer" includes a multi-layer thermal hand warmer formed by combining two or more thermal hand warmers.
[0017] Sodium chloride may be either rock salt or seawater-derived salt, but it is more preferable that it contains moisture equivalent to about 1% by weight. Seawater-derived salt is preferably used, and examples of such salts include those commercially available as sun-dried salt, sea salt, and coarse salt. Note that seawater-derived salt may contain trace amounts of bittern and impurities. Sodium chloride with a high porosity of about 50% to 90% is preferably used. The preferred angle of repose for sodium chloride is 40° to 70°.
[0018] One or more waste-derived, natural, or animal-derived materials may be selected and mixed from the following group: for example, sea glass, silica sand, quartz, and other waste-derived, natural, or animal-derived silicate-containing components; sea sand from beaches around the world or in Japan, crushed ceramics, or discarded gemstones; porous or non-porous calcium carbonate-containing components from waste-derived, natural, or animal-derived materials such as coral sand, coral fragments, seashells, discarded pearls, and pearl powder; and calcium phosphate-containing components from waste-derived, natural, or animal-derived materials such as human or animal bones (powder), teeth (powder), and horns (powder). In this specification, aluminosilicate-containing components are components containing compounds in which some of the silicon atoms in the silicate are replaced with aluminum atoms, and are conceptually distinct from silicate-containing components. However, silicate-containing components may contain trace amounts of aluminum to the extent that it does not affect the composition formula.
[0019] When used in a hand warmer, the above composition preferably contains 70-85% by weight of sodium chloride and 15-30% by weight of one or more waste-derived, natural, or animal-derived materials, based on the total weight of the composition. A more preferable lower limit for sodium chloride is 73% by weight.
[0020] The specific combinations of components in the above composition are not particularly limited, and examples include salt / coral fragments / coral sand, salt / coral sand / bone meal (bone ash), salt / quartz / bone meal, salt / sea glass / shell meal / bone meal, salt / pearl powder / coral sand, salt / coral sand / silica sand, salt / coral sand / silica sand / bone meal, salt / gemstone waste, etc. Among these, two-component, three-component, or four-component compositions containing salt and coral sand are preferred from the viewpoint of water retention and heat retention. When sea sand, coral, or coral fragments are added, it is preferable to use only very small amounts of material with a particle diameter of approximately 2 mm or less, preferably 1 mm or less, similar to star sand, in order to prevent charring of the outer coating which is thought to be caused by abnormal heating. Here, the particle diameter is the average value of the circular equivalent diameter of the particle image obtained by the image analysis method.
[0021] The porosity of sodium chloride and one or more waste-derived, natural, or animal-derived materials can be considered an indicator of the content of air layers with low thermal conductivity. However, when used for heating by spraying water, the heat stored by the water has a greater impact on heat retention, so the porosity does not have much impact on heat retention. Therefore, the range of porosity is not particularly limited, but it can be 50% to 90%. A preferred lower limit is 60%, a preferred upper limit is 88%, and the upper limit can also be 80% or less. When using multiple components, it is preferable that the porosity of each component be about the same from the viewpoint of improving mixability. Note that the porosity in this specification is a value calculated by the ratio of bulk density to true density.
[0022] When comparing the temperature immediately after removing a mixture of coarse salt (sodium chloride), bone ash (containing calcium phosphate), silica sand (containing silicate), or coral sand (containing calcium carbonate) from a microwave oven, and how slowly it cools down, the following trends may be observed under certain conditions. (1) In terms of resistance to cooling at the same mixing ratio, calcium phosphate >> silica sand > coral sand, and the temperature immediately after removing from the microwave at the same mixing ratio generally tends to be coral sand > silica sand > calcium phosphate (Figure 1). (2) Mixtures of sodium chloride and silica sand tend to have little change in their resistance to cooling, regardless of the relatively wide range of silica sand content, from 10% to 25% by weight. (3) Mixtures of sodium chloride and coral sand, particularly those with a salt-to-coral ratio of 80:20 or 75:25, have properties that make them difficult to cool (Figure 2). (4) A mixture of sodium chloride and calcium phosphate tends to cool more slowly as the proportion of calcium phosphate increases.
[0023] The above composition is not limited to waste-derived, natural, or animal-derived materials as described above, and may contain 70-85% by weight of sodium chloride and 15-30% by weight of one or more components selected from calcium carbonate, calcium phosphate, and silicates, based on the total weight of the composition. In the case of three or four components, preferably, the composition contains 70-85% by weight of sodium chloride, 10-18% by weight of porous calcium carbonate, and 5-12% by weight of calcium phosphate and / or silicates, based on the total weight of the composition. Increasing the proportion of silicates tends to increase the temperature immediately after heating, and increasing the proportion of calcium phosphate tends to make it difficult to cool down, so it is preferable to adjust this with an outer coating.
[0024] The heated hand warmer of the present invention is surrounded by a flame-retardant sheet. In this specification, "flame-retardant sheet" means a sheet that satisfies at least one of the conditions of Category 3 in the JIS L 1091A-3 method and an oxygen index value of 25 or higher in JIS K7201, or a sheet that exhibits flame retardancy of any of the A, B, or C types in the JIS A 1323 flame retardancy test method. The sheet is not particularly limited as long as it is a structure that can surround the composition, and one or more sheets of woven fabric, nonwoven fabric, knitted fabric, a sheet in which all or part of the fibers have melted and become one, a rubber sheet, etc. can be used.
[0025] As materials for flame-retardant sheets, organic materials and / or inorganic materials can be used individually or in combination. Examples of organic materials include polyarylate cloth, aramid cloth, polyester cloth, felt containing carbonized fibers (carbon fibers) regardless of whether they are PAN-based or pitch-based (hereinafter also referred to as "carbonized felt"), carbon cloth, urethane rubber, silicone rubber, composite materials of silicone rubber and linen cloth, composite materials of silicone rubber and aramid cloth, etc. Examples of inorganic materials include glass fiber sheets, glass felt, rock wool, refractory ceramic fiber sheets, AES fiber sheets, silica fiber sheets, alumina fiber sheets, glass wool, etc.
[0026] The thickness of the flame-retardant sheet can be adjusted according to the composition, and empirically, thicker sheets tend to be less likely to cause low-temperature burns and to cool down more slowly.
[0027] Flame-retardant sheets are typically sewn together into a bag shape using flame-retardant thread made of the same material as the flame-retardant sheet. Examples of flame-retardant thread materials include those exemplified above for the flame-retardant sheet, with para-aramid thread being preferred for strength and meta-aramid thread being preferred for cost.
[0028] When layering two flame-retardant sheets, possible combinations of materials for the inner flame-retardant sheet / outer flame-retardant sheet / flame-retardant yarn include, for example, para-aramid fabric / carbonized felt / aramid yarn, meta-aramid fabric / para-aramid fabric / aramid yarn, meta-aramid fabric / carbonized felt / aramid yarn, carbonized felt / carbonized felt / aramid yarn, and carbonized felt / para-aramid fabric / aramid yarn.
[0029] In one embodiment, the sheet may be coated / impregnated with an inorganic or heat-resistant resin. In one embodiment, the sheet is preferably made of a water-permeable material. The water-permeable material can withstand heating and heat retention conditions such as those of a microwave oven or heating device, and can supply moisture to the surface of the composition containing the sheet.
[0030] In one embodiment, a heat pack can be manufactured by sandwiching the above-mentioned composition between two larger pieces of felt and sewing the four sides of the felt together with an overlock stitch using a serger and the above-mentioned flame-retardant thread. In one embodiment, a heat pack can be manufactured by folding an aramid cloth in half along its long side, overcasting both sides with a serger, turning it inside out to create an opening bag, placing the felt surrounding the composition inside the opening bag, folding the opening of the bag inward, and overcasting it with household sewing thread.
[0031] A heat pack wrapped in a water-permeable material is useful when stored in a resealable, water-impermeable bag. A plastic zipper bag can be used as the resealable, water-impermeable bag due to its flexibility and the ability to integrate it with the outer bag. A typical example is Ziploc®. However, heat resistance is required for long-term storage (3-4 months) in a heating device or for repeated heating in a microwave oven. Therefore, especially for repeated heating in a microwave oven, it is recommended to remove the heat pack wrapped in the water-permeable material, heat it, and then return it to the bag, or to use other heat-resistant, water-impermeable bags made of polypropylene, silicone rubber, etc.
[0032] The heat pack 10 shown in Figure 4 encases the above-mentioned composition in a water-permeable material 2 and is stored in a water-impermeable bag 4 that can be sealed with a zipper 3. The water-impermeable bag 4 is placed inside an outer bag 6. The outer bag 6 is not limited to what is generally called a bag, but can be anything that wraps the outside, and includes stuffed animals, belly warmers, amulets, pillowcases, etc. The material of the outer bag is not particularly limited, but when a plastic zipper bag is used as the water-impermeable bag, laminated fabric that can be fused to the zipper bag is preferably used. In this case, it is preferable that the outside of the laminated fabric be treated with a water-repellent coating to prevent staining. In addition, if softness of texture is important, silk, gauze, double gauze, etc. can also be used.
[0033] The outer bag 6 and the airtight, water-impermeable bag 4 may or may not be integrated. If they are integrated, with the airtight portion (zipper) closed, both sides are covered with laminated fabric, and as shown in Figure 5a, the three sides of the airtight portion excluding the opening side 5 are heat-sealed together with the laminated fabric, leaving a fusion allowance of about 5 mm to 10 mm at the end of the airtight portion as a fusion allowance 7.
[0034] A heat-retaining material 8 may be provided between the outer bag 6 and the airtight, water-impermeable bag 4, as shown in Figures 5b and 5c. Examples of heat-retaining material 8 include felt, double gauze, and plastic cushioning sheets for food shelves.
[0035] When inserting a heat-insulating material 8 between the outer bag 6 and the airtight, water-impermeable bag 4, it is preferable to heat-seal the heat-insulating material 8 together with the outer bag 6, as this prevents any displacement of the heat-insulating material 8. As a result of heat sealing, the state is as shown in Figure 5d. In this embodiment, a tabletop sealer (Fuji Impulse Sealer Co., Ltd., T-130 model) is used as the sealer for heat sealing.
[0036] The method of using the heat pack of the present invention includes spraying water onto the surface of the heat pack wrapped in the water-permeable material to the extent that the center of the heat pack does not become damp, and heating or keeping it warm in a microwave oven or heating device. Here, the amount of water sprayed is preferably 0.5 to 5% by weight of the total weight of the composition. A more preferable upper limit is 3% by weight, and an even more preferable upper limit is 2.5% by weight. For microwave heating, if the total weight of the composition is slightly less than 100g, the guideline is 1 minute 30 seconds to 2 minutes at 500W, or 40 seconds to 1 minute 30 seconds at 900W. As a heating device, a hot towel warmer, generally called a hot cabinet or towel warmer, is preferably used.
[0037] As shown in Figures 12 and 13, the multilayer heat pack 11 of the present invention has a cloth storage bag 12 with two partition cloths 14a and 14b inside to form three pockets. The heat pack 20 is stored in the first pocket 13 and the third pocket 15, and a coral 22 surrounded by a heat-resistant material 18 is stored in the second pocket 17. The heat-resistant material shown in Figure 14 is a packaging material for coral that is used to prevent the coral from scorching when heated in a microwave oven, as the coral can become hot. In this embodiment, a spatter sheet made of carbonized fiber is used for curing. Other heat-resistant materials that can be used include, for example, urethane rubber, glass fiber sheets, silicone rubber, a composite material of silicone rubber and linen, a composite material of silicone rubber and aramid fiber sheets, and polyester sheets. The partition cloths are not essential as long as they can stabilize the state in which the heat-resistant material surrounding the coral is sandwiched between the heat packs. [Examples]
[0038] Example 1 (Salt) Place 220g of edible salt into a Tupperware container (12cm long x 8cm wide x 3cm high), level one-fillet container, creating a height of approximately 3cm inside the container (bulk density 0.76g / cm³). 3 , true density: 2.16g / cm 3 The mixture was spread until it reached a porosity of 64.8%, and the surface was sprayed with water 50 times using a spray bottle (10cc of spray, 4.5% by weight relative to the weight of the edible salt). Then, it was heated in a 900W microwave oven for 2 minutes. After that, with the lid of the container open, the temperature change over time was measured using a commercially available digital thermometer (DRETEC O-274IV cooking thermometer), with the core temperature considered to be at a depth of approximately 2cm from the surface and the surface temperature at a depth of approximately 1cm from the surface. The results are shown in Table 1.
[0039] Example 2 (Coral Sand 1) Instead of salt, use 220g of coral sand, which is mainly composed of calcium carbonate, to a height of approximately 2.6cm in the container (bulk density 0.88g / cm³). 3 , true density: 2.7~2.9g / cm 3The coral sand was spread until the porosity reached 67.4% to 70.0%, and water was sprayed 50 times (10cc spray volume, 4.5% by weight relative to the weight of the coral sand). Otherwise, the temperature change over time was measured in the same manner as in Example 1. The results are shown in Table 1.
[0040] Example 3 (Coral Sand 2) In this experiment, 220g of coral sand was used instead of salt, and it was spread to a height of approximately 2.6cm inside the container. The entire container was then moistened by spraying it with water more than 200 times. Otherwise, the temperature change over time was measured in the same manner as in Example 1. The results are shown in Table 1.
[0041] Example 4 (Silica Sand) Instead of salt, I used 220g of beach sand collected from Yoron Island, which is about 2.8cm high in the container (bulk density 0.82g / cm³). 3 , true density: 2.5g / cm 3 The material was spread until a porosity of 67.2% was achieved, and water was sprayed on it. The temperature change over time was measured in the same manner as in Example 1. The results are shown in Table 1.
[0042] [Table 1]
[0043] As can be seen from Table 1, the salt in Example 1 showed little difference between the core and surface temperatures. In Example 2, coral 1's core temperature dropped sharply by 36 degrees Celsius within 5 minutes of the start of measurement, but the subsequent rate of temperature decrease was the slowest among the three types. The sand in Example 4, like coral 1, showed a sharp drop of 39 degrees Celsius in its core temperature within 5 minutes of the start of measurement, the lowest temperature among the three types. In a comparison between Example 2 and Example 3, it was expected that the temperature of coral sand 2, which retained a good amount of moisture, would rise when microwaved, but it did not rise as much as expected, and the inside of coral 1, which should have been almost dry, was hotter. In a comparison between Example 2 (coral 1) and Example 4 (silica sand), despite having almost the same porosity in a dry state, there was a significant difference in heat retention, suggesting that the material and its resulting water retention have a greater influence than porosity.
[0044] Visual observation of its properties revealed that salt reaches the highest temperature when heated while retaining moisture, but it solidifies if heated too much, making it unsuitable for use in hand warmers if too much water is added.
[0045] Example 5 Using coral sand 3, which was obtained by directly passing water through it and then draining the water, rather than using a spray bottle, and which had a higher moisture content than coral sand 2 in Example 3, we varied the heating time in a 900W microwave oven and measured the temperature immediately after removing it from the microwave. The results are shown in Table 2.
[0046] [Table 2]
[0047] Table 2 shows that, regardless of the heating time, the temperature of the deeper part of coral sand 3 was higher than that of the surface, indicating that heat was being transferred from the deeper part to the surface. Furthermore, the temperature of the deeper part of coral sand 3 plateaued at around the boiling point of water after 1 minute and 30 seconds, indicating that the added energy was being used as latent heat when the water that fell to the deeper part due to gravity evaporated. From the results of Examples 2 and 3 and Table 2, it was found that coral sand tends not to heat up easily when it contains too much moisture, and does not heat up further when the moisture is gone. Therefore, it is important to spray water on the surface just enough so that the center of the heat pack does not become damp. This result is advantageous because fewer sprayings are required, making the process simpler. In light of the results of Example 5, in Example 2, the reason why the surface reached near the boiling point of water immediately after being removed from the microwave, while the deep part rose above the boiling point of water, is thought to be that in the deep part, where there is almost no water, the specific heat of calcium carbonate and air (values of limestone are 920 J / Kg / °C, and air is about 1000 J / Kg / °C) is about one-quarter of the specific heat of water (4189 J / Kg / °C), causing a rapid temperature increase.
[0048] Based on the above considerations, it was speculated that a mixture of salt and coral sand that retains a slightly moist level of moisture might be suitable for a warming pouch, because of the salt inside in a state where the surface is wet and the relatively high internal temperature of the coral 1 in a state where the surface is wet.
[0049] Example 6-1 (Calcium Phosphate) As the calcium phosphate-containing component, 110 g of commercially available natural bone ash (manufacturer: Takekuro Seiko Co., Ltd., product number: product code TO804013) was spread in a tapper (vertical 12 cm × horizontal 8 cm × height 3 cm) to a height of about 2.5 cm (bulk density 0.46 g / cm 3 , true density: 3.14 g / cm 3 , porosity: 85.4%). After spraying water 50 times (Example 6-1) or 230 times (Example 6-2) on the surface by atomization, it was heated in a 900 W microwave oven for 2 minutes. Then, with the lid of the tapper open, a commercially available digital thermometer (DRETEC O-274IV cooking thermometer) was inserted near the center and near the surface, the time change of the temperature T was measured, and the properties were visually observed. The results are shown in Table 3. The time change of the temperature was tentatively curve-fitted by the least squares method using the following model formula with T0 and B as variables. (Hereinafter, unless otherwise specified, T0 is the deep layer temperature value immediately after taking out the range, T ∞ is the indoor temperature controlled constantly, B means the coefficient of the following formula, and σ 2 is the error variance). B was used as an index of the difficulty of cooling. T=T ∞ +(T0 - T T ∞ )exp(-Bt) Example 6-2 The surface was sprayed with water 230 times by atomization to wet the deep layer part, and then the time change of the temperature was measured and the properties were visually observed in the same manner as in Example 6-1. The results are shown in Table 3. Example 6-3 The time change of the temperature was measured and the properties were visually observed in the same manner as in Example 6-1, except that the surface was not sprayed with water. The results are shown in Table 3.
[0050]
Table 3
[0051] According to Table 3, in Example 6-2, the deep-sea temperature was highest during the first 20 minutes, while in Example 6-3, the deep-sea temperature was highest from the second 20 minutes onward. Furthermore, in Example 6-1, the surface temperature decreased rapidly, while in Example 6-2, the surface temperature was highest during the first 20 minutes. Overall, immediately after heating, the temperature of Example 6-2, which retained moisture, was higher, but the powdered Example 6-3 tended to cool slightly more slowly.
[0052] Generally, the most effective heat retention comes from the air layer (thermal conductivity 0.025-0.030 W / m / K), and thermos flasks achieve insulation and heat retention by eliminating this air layer and creating a vacuum. Considering this, it can be expected that a dry material with high porosity will have better heat retention because air is contained between the particles, creating an air layer. In other words, the temperature in the center will be high, but the air layer will retain heat, making it difficult for heat to transfer to the outside, and the temperature felt will not be hot. Example 6-3 exhibited precisely these characteristics.
[0053] On the other hand, in Example 6-2, the reason why the deep-sea temperature was highest in the first 20 minutes when there was a lot of moisture is thought to be because, unlike in Example 6-3, it was retaining heat by utilizing the material's inherent water retention properties and the heat-storing properties of water. Looking at the results of Example 6-1 in Table 3, despite having a higher porosity than coral and sand, the heat dissipation in the deep layer was significant, suggesting that when heating by spraying water, factors such as material properties and water retention have a greater influence than porosity.
[0054] Furthermore, it was found that calcium phosphate hardens when it comes into contact with water, so this should also be taken into consideration when incorporating it into a mixture.
[0055] Example 7 (Measurement with varying ratios of salt and calcium phosphate) A total of 100g of coarse salt (origin: Setouchi coarse salt, manufacturer: Salt Company Co., Ltd.) and calcium phosphate were placed in a nonwoven fabric measuring approximately 17cm x 11.5cm. The fabric was then folded in half lengthwise (approximately 8.5cm x 11.5cm) and heated in a 900W microwave for 1 minute. As shown in Figure 6, the fabric was removed, placed on newspaper, the folded part was unfolded, and a thermometer was inserted. The results of the temperature change over time are shown in Table 4.
[0056] [Table 4]
[0057] Table 4 shows that the temperature and heat retention were highest immediately after removal from the microwave when the calcium phosphate content was 85%. This suggests that when using a composition of multiple components, it is necessary to consider the possibility of an appropriate mixing ratio. Furthermore, since moisture seeped out of the nonwoven fabric immediately after heating, it is suggested that when using it as a heat pack, it is appropriate to place the nonwoven fabric bag containing the composition inside another water-repellent and heat-resistant bag.
[0058] Example 8 (Measurement with varying ratios of salt and coral) A total of 100g of salt and coral was placed in a non-woven fabric measuring approximately 17cm x 11.5cm, sprayed with water 50 times, folded in half lengthwise (approximately 8.5cm x 11.5cm), and heated in a 500W microwave for 1 minute and 30 seconds. As shown in Figure 6, it was removed, placed on newspaper, the folded part was unfolded, and a thermometer was inserted. The results of the temperature change over time are shown in Table 5. The ambient environment was 25 degrees Celsius and 51% humidity.
[0059] [Table 5]
[0060] Table 5 shows that as the proportion of coral increases, the food retains heat more slowly, while the temperature immediately after removing it from the microwave decreases. Overall, for the first 30 minutes, the 10% coral content resulted in better heat retention than the 30% coral content. Combining Examples 7 and 8, it is suggested that when creating a multi-component composition that does not harden on the surface, an appropriate blending ratio exists within the range of 5-20% by weight of waste-derived, natural, or animal-derived materials, regardless of the material or porosity.
[0061] Example 9 (Beaker / Coral) 100g of pure coral sand, or a composition obtained by thoroughly mixing coarse salt and coral sand in a predetermined ratio, was placed in a 150cc beaker to a total of 100g. The beaker was then heated for 1 minute in a 900W microwave oven with two paper plates placed on top of each other. After heating, as shown in Figure 7, a cooking thermometer (DAISO C008, glass, indicator: kerosene) was inserted upright in the center and then tilted over the spout of the beaker. The gap in the contents created when the thermometer was tilted was covered and filled. This procedure ensured that the thermometer's position remained unchanged, was set to approximately the same position, and allowed observation without moisture seeping into the nonwoven fabric or moving it even a millimeter. The measurement results of the temperature change over time are shown in Table 6. The ambient environment was set to an air conditioner temperature of 22 degrees Celsius and a humidity of 35%.
[0062] [Table 6]
[0063] Table 6 shows that the mixture ratios of 80 parts salt to 20 parts coral, or 75 parts salt to 25 parts coral, exhibited particularly poor cooling properties. This tendency was also observed in Example 8, which used nonwoven fabric, suggesting that this property originates from the mixed composition, regardless of whether the outer container is made of nonwoven fabric or a beaker.
[0064] Example 10 (Beaker / Calcium Phosphate) Except for using calcium phosphate powder instead of coral sand, the procedure was the same as in Example 9, and the change in temperature over time was observed. The results are shown in Table 7. The ambient environment was a set temperature of 22 degrees Celsius with a humidity of 35%.
[0065] [Table 7]
[0066] Table 7 shows that as the proportion of calcium phosphate increases, the temperature tends to stay higher.
[0067] Example 11 (Beaker / Silica Sand) The temperature change over time was observed in the same manner as in Example 9, except that silica sand was used instead of calcium phosphate powder. The results are shown in Table 8. The ambient environment was set to an air conditioner temperature of 22 degrees Celsius and a humidity of 35%.
[0068] [Table 8]
[0069] Table 8 shows that while the retention of heat remained consistent across a relatively wide range of silica sand content (10% to 25% by weight), a higher proportion of silica sand tended to result in a lower temperature immediately after removal from the microwave. However, using only silica sand (11) resulted in a dramatic decrease in temperature immediately after removal from the microwave. This is thought to be due to the absence of moisture in the silica sand itself.
[0070] In summary, the results of Examples 9 to 11, conducted under the moisture conditions of coarse salt, show that in terms of resistance to cooling at the same mixing ratio, calcium phosphate >> silica sand > coral sand, and the temperature immediately after removal from the microwave at the same mixing ratio generally follows the pattern of coral sand > silica sand > calcium phosphate.
[0071] Example 12 (Beaker / 3, 4 components) Based on the results of the above-mentioned Examples 9 to 11, heat dissipation tests were conducted under the same conditions as in Example 9, using the three-component and four-component compositions listed in Table 9. The results are shown in Table 9. The ambient environment was set to an air conditioner temperature of 22 degrees Celsius and a humidity of 35%.
[0072] [Table 9]
[0073] Table 9 shows that (23) and (24) were both equally good in terms of how well they retained heat, but the difference in temperature immediately after removal resulted in a difference in temperature after one hour. A comparison between (23) and (25) revealed that replacing all of the calcium phosphate with silica sand dramatically increased the temperature immediately after removing from the microwave.
[0074] Example 13 (Cushioned beaker / 3, 4 components) As shown in Figures 8 and 9, a heat dissipation test was conducted under the same conditions as in Example 12, except that a polyethylene food shelf cushion sheet was wrapped around the material four times. The results are shown in Table 10. The ambient environment was set to an air conditioner temperature of 22 degrees Celsius and a humidity of 35%.
[0075] [Table 10]
[0076] Table 10 shows that, compared to Table 9 of Example 12 before the cushioning, the σ levels are consistently the same. 2 The value of decreased, indicating that blocking heat dissipation from the beaker glass brought the experiment closer to an ideal environment. While the three-component and four-component compositions (27), (28), (29), and (31) were low in temperature immediately after being removed from the microwave, they all tended to cool down slowly. In contrast, the coarse salt, coral, and silica sand composition (30) showed a high temperature immediately after being microwaved, but cooled down somewhat quickly, similar to the trend observed in Example 12. Furthermore, a comparison with the B value in Table 9 revealed that the samples generally cooled down more slowly.
[0077] Example 14 (Investigation of the amount of water required to cause loss of performance in coarse salt) Two types of beakers were used: a standard beaker (Beaker 1) containing a total of 100g of coarse salt in a 150cc beaker, and a beaker (Beaker 2) wrapped in polyethylene food shelf cushioning sheet. Both were heated for 1 minute in a 900W microwave oven with two paper plates placed on top. After heating, as shown in Figure 7, a cooking thermometer (DAISO C008, glass, indicator: kerosene) was inserted upright into the center and tilted so that it fit into the spout of the beaker. The gap in the contents created when the thermometer was tilted was covered and filled, and the change in temperature over time was measured. Here, "moist" was used as the coarse salt without any treatment, and "dry" was used as the salt after repeating the process of heating in a 900W microwave for 1 minute four times, resulting in a weight of 99g after 1% of the moisture had been removed. The results are shown in Table 11. The ambient environment was an air conditioner set to 22 degrees Celsius and a humidity of 35%.
[0078] [Table 11]
[0079] Comparing the B values of beaker 2 (34) and (35) in Table 11, it appears that even if 1% of the water is removed from the coarse salt, there is no significant change in how slowly it cools down. However, the temperature immediately after removing it from the microwave drops significantly, and it becomes impossible to obtain satisfactory characteristics as a hand warmer. Conversely, it is suggested that sufficient characteristics can be maintained as long as the salt component always retains 1% moisture.
[0080] Example 15 (Investigation of the amount of water required to restore the performance of coarse salt) In both cases, 99g of dry coarse salt was placed in 150cc beakers 1 and 2, and the temperature immediately after removal from the microwave was compared after spraying with a spray bottle 5 times (equivalent to 1cc) and 10 times (equivalent to 2cc). The results are shown in Table 12. The ambient environment was an air conditioner set to 22 degrees Celsius and 35% humidity.
[0081] [Table 12]
[0082] Table 12 shows that the properties of coarse salt can be restored with 5 sprays of mist, but even with 10 sprays, there is almost no change in temperature immediately after removing from the microwave. This suggests that if a hand warmer is placed in a non-permeable bag beforehand and excess mist is sprayed on, it may be possible to reuse the product after repeated microwave heating.
[0083] Example 16 (Cushioned beaker / 3, 4 components) A heat dissipation test was conducted under the same conditions as in Example 13. The results are shown in Table 13. The ambient environment was a set temperature of 22 degrees Celsius and a humidity of 35%.
[0084] [Table 13]
[0085] Table 13 shows that (41) has a lower temperature immediately after use than (40), but there is no significant difference after 5 minutes, so (41) is considered to be safer to use.
[0086] Example 17 (Comparison of temperature changes between nonwoven fabric surface temperature and core temperature) A nonwoven fabric bag was filled with a total of 100g of salt, coral sand, calcium phosphate, and silica sand, and heated for 1 minute in a 900W microwave oven with two paper plates placed on top of each other. After heating, as shown in Figure 10, a cooking thermometer (DAISO C008, glass, indicator: kerosene) was immediately inserted into the center of the nonwoven fabric bag, and another thermometer was placed on the surface of the nonwoven fabric bag and secured with duct tape. The nonwoven fabric bag was then placed over the surface thermometers, and a heat dissipation test was conducted. The results are shown in Table 14. The ambient environment was an air conditioner set to 22 degrees Celsius and a humidity of 35%.
[0087] [Table 14]
[0088] Table 14 shows that after 5 minutes, the heat gradually transferred from the inside to the nonwoven fabric, resulting in a higher surface temperature. The surface temperature immediately after exposure was 44°C to 58°C, but it is thought to be even higher. According to various literature, low-temperature burns are said to occur when exposed to an object at 44°C for 3 to 4 hours, an object at 46°C for 30 minutes to 1 hour, or an object at 50°C for 2 to 3 minutes. From this perspective, it was found that direct contact with (46), (47), (49), and (50), which contain silica sand, is not advisable in the initial stages of heat dissipation, and temperature control with a cloth cover or the like is necessary. However, it was found that the risk of low-temperature burns is low for materials that do not contain silica sand.
[0089] Example 18 (Comparison of core body temperature and perceived temperature) A non-woven fabric bag was filled with a total of 100g of salt, coral sand, calcium phosphate, and silica sand. It was then heated for 1 minute in a 900W microwave oven with two paper plates placed on top of each other. After heating, the bag was immediately removed, and a cooking thermometer (DAISO C008, glass, indicator: kerosene) was inserted into the center of the bag as shown in Figure 11. The opening of the bag and the thermometer were then closed by gripping them together, and the temperature and perceived temperature of the part containing the mixture were recorded. When touching the bag, the hand that was less warm was used as much as possible. The results are shown in Table 15. The ambient environment was an air conditioner set to 22 degrees Celsius and a humidity of 35%.
[0090] [Table 15]
[0091] Table 15 shows that, when compared with the temperatures obtained in the deep temperature and surface temperature experiment of Example 17, the deep temperature that felt lukewarm to the touch lasted for about 20 to 30 minutes.
[0092] Example 19 (A heat pack in which the composition is wrapped in felt made of flame-resistant polyacrylonitrile fibers) Sodium chloride purified by the ion exchange membrane method and coral sand were blended in a weight ratio of 7:3 and sandwiched between two layers of flame-resistant polyacrylonitrile fiber felt (product number: Carbon Felt PC-400, manufactured by Osaka Seisakusho Co., Ltd., JIS A-1323 Class A compliant). The edges were then sewn together using a serger (baby lock Ihojin Special 550, thread used: high heat-resistant meta-aramid fiber #50 / 3000 (Conex, Teijin), stitching method: 2-needle 4-thread overlock). After lightly misting the resulting heat pack shown in Figure 15 with water, it was wrapped in a gauze towel and heated in a 600W microwave for 2 minutes before being removed. Immediately afterward, the surface of the towel was damp, and it felt hot enough to cause a low-temperature burn if the temperature remained the same. However, after 5 minutes, when the surface of the towel dried, the temperature became appropriate, and it felt lukewarm to the touch for about 20 to 30 minutes. Upon undoing the stitching and opening the package, no burns or other damage were observed inside.
[0093] Example 20 (A heat pack in which a composition containing coral stone is wrapped in felt made of flame-resistant polyacrylonitrile fibers) In Example 19, small coral stones with a particle diameter of approximately 2mm to 4mm and salt were placed in a felt bag made of flame-retardant polyacrylonitrile fiber, wrapped in a towel, sprayed with water, and then heated in a microwave oven. This process was repeated before use. As a result, the small coral stones with a particle diameter of approximately 2mm to 4mm were heated together with the salt inside the felt, causing the coral stones to become hot. The carbonized fibers did not burn, but the carbonized fibers continued to make contact with a single point on the towel, causing the towel to burn as shown in Figure 16. Therefore, charring was not observed when the coral stones were surrounded by felt alone. However, depending on the material of the felt outer covering, it is preferable to avoid using coral stones with a particle diameter of 2mm to 4mm or larger, or to shorten the heating time.
[0094] Example 21 (A hand warmer in which a composition containing coral stone is wrapped in a cotton bag and cotton material) We placed small coral sand particles (less than 2mm in diameter) and salt into a cotton bag about the thickness of bleached cotton cloth, wrapped it in a thick canvas cotton material, misted it with water as needed to dry it, and then heated it in a microwave at 600W for 1 minute. This process was repeated before use. As a result, even after a year, the cotton bag and cotton material did not scorch.
[0095] Example 22 (A hand warmer in which a composition containing coral stone is wrapped in a cotton bag and linen material) We placed small coral sand particles (less than 2mm in diameter) and salt into a cotton bag about the thickness of bleached cotton cloth, double-wrapped it in hemp material, misted it with water as needed to dry it, and then heated it in a microwave at 600W for 1 minute before use. This process was repeated. As a result, even after a year, neither the cotton bag nor the hemp material was scorched.
[0096] Example 23 (A hand warmer in which a composition containing coral stone is wrapped in a burlap sack and cotton material) We placed small coral sand particles (less than 2mm in diameter) and salt into a hemp bag about the thickness of bleached cotton cloth, wrapped it in thick canvas cotton material, misted it with water as needed to dry it, and then heated it in a microwave at 600W for 1 minute, repeating this process before use. As a result, even after a year, the hemp bag and cotton material did not scorch.
[0097] Example 24 (A hand warmer in which a composition containing coral stone is wrapped in a burlap sack and double-layered burlap material) We placed small coral sand particles (less than 2mm in diameter) and salt into a hemp bag about the thickness of a bleached cotton cloth, double-wrapped it with hemp material, misted it with water as needed to dry it, and then heated it in a microwave at 600W for 1 minute before use. This process was repeated. As a result, even after a year, the hemp bag and hemp material did not scorch.
[0098] Example 25 (A heat pack in which a composition containing coral stone is wrapped in a burlap sack, burlap material, and cotton-burlap blend material) Small coral sand particles (less than 2mm in diameter) and salt were placed in a hemp bag about the thickness of bleached cotton cloth. This bag was then wrapped in hemp material and a cotton-linen blend material of similar thickness. After misting it with water as needed during drying, it was heated in a microwave at 600W for 1 minute and used repeatedly. As a result, even after one year, the hemp bag, hemp material, and cotton-linen blend material did not scorch.
[0099] Example 26 (Durability test of heat packs using various packaging methods) Sodium chloride purified by ion exchange membrane method and coral sand were mixed in a weight ratio of 7:3, to which silica sand or coral stone was added as appropriate. The mixture was then placed in PP nonwoven fabric and PP plastic bags and packaged in Ziploc® bags. After repeated use in a hot cabinet for 6 months to 1 year and 4 months, the condition of the contents was checked. The results are shown in Table 16 and Figures 17 to 22.
[0100] [Table 16]
[0101] PP nonwoven fabric and PP plastic bags, regardless of the composition of their contents, deteriorated due to thermal degradation after repeated use and insulation in a hot cabinet for over a year. Japanese-made hot cabinets provided a more comfortable temperature, suggesting that the difference between the manufacturer's set temperature and the actual temperature may also be a factor in the rate of deterioration. Items (4) and (5), which had their edges sealed, were considered to have relatively good durability because they did not come into contact with water.
[0102] Example 27 (Durability test of a heat pack using a cotton bag or burlap bag) A composition of 85g of sodium chloride mixed with 15g of coral sand was placed in a cotton bag or burlap bag, and then wrapped in cotton, burlap, or cotton-linen blend material and heated in a microwave oven at 600W for 1 minute. Immediately after removal, the changes in surface temperature of the cotton, burlap, or cotton-linen blend material and the internal temperature of the composition over time were measured, as shown in Figure 23. The results are shown in Tables 17 and 18. The procedures for the second, third, and fourth trials were as described in the table, but only the temperature immediately after heating was measured. [Table 17] [Table 18]
[0103] Example 28 (A heat pack in which the composition is wrapped in felt made of flame-resistant polyacrylonitrile fibers, and then wrapped in aramid cloth) A piece of aramid cloth (Kevlar®) cut to 20cm x 50cm was folded in half along its longest side, and both sides were overlocked. The cloth was then turned inside out to create an opening bag, into which a piece of felt containing 580g of the composition (salt:coral = 78:22) was placed. The opening of the bag was folded inward by about 1cm and overlocked with household sewing thread (product name: Nannen thread, manufactured by Fujix). The entire process is shown in Figures 24A and 24B. The resulting heat pack was lightly misted with water, wrapped in a gauze towel, and heated in a 600W microwave oven for 2 minutes before being removed. Immediately afterward, the surface of the towel was damp, and it felt hot enough to cause a low-temperature burn if the temperature remained the same. However, after 5 minutes, the surface of the towel dried, and the temperature became comfortable. The lukewarm feeling lasted for about 20-30 minutes. Upon undoing the stitching and opening the package, no burning or charring was observed inside. Furthermore, even when heated at the wrong wattage (e.g., 1000W) or when the heating time was extended to make it hotter, it did not burn.
[0104] It should be noted that the embodiments of the present invention are not limited in any way to those described above, and not all of the configurations described in the above embodiments are necessarily essential requirements of the present invention. The present invention can take various forms, such as modifications, as long as they do not depart from its technical spirit and fall within that technical scope. [Industrial applicability]
[0105] The present invention's heated hand warmer can be used at home while sleeping, placed inside a belly band, or kept warm in a hand towel warmer and offered to customers as a neck pillow during shampooing in beauty salons, as a neck pillow during shaving in barbershops, or as a neck pillow or abdominal support during waiting times or treatments in dental clinics. It can also be heated in a microwave oven and used in school infirmaries. Furthermore, it is expected to have applications in acupuncture clinics, beauty salons, osteopathic clinics, and chiropractic clinics. In addition, even in situations where microwave ovens are unavailable, such as during camping or disasters, or when there is no electricity or supplies, it can be used by placing it on a cooking sheet and heating it on a BBQ griddle or frying pan, placing it in an impermeable bag and heating it in a water bath, or wrapping it in aluminum foil and placing it over a fire. Moreover, since the manufacturing process of the heated hand warmer itself is simple, it can be used as a job in sheltered workshops, creating employment and making it industrially useful. The present invention's heated hand warmer, by using pet bones or human bones as components, offers a new form of keeping a memento of a deceased pet or loved one close at hand. [Explanation of Symbols]
[0106] 10, 20 Heated hand warmers (heated hand warmers) 2. Water-permeable material 3. Sealing area (zipper) 4 Impermeable bag 5 Opening edge 6. Outer bag 7. Fusion 8 Heat retention material 11. Multilayer Heat Pack 12 fabric storage bags 13 First Pocket 14a, 14b Partition fabric 15. Third pocket 17. Second pocket 18 Heat-resistant materials 22 Coral
Claims
1. A hot pocket warmer surrounded by a sheet satisfying at least one of the conditions of Category 3 according to the JIS L 1091A-3 method and an oxygen index value of 25 or more according to the JIS K7201, or a sheet showing any one of Class A, Class B, or Class C flame retardancy according to the JIS A1323 flame retardancy test method, wherein the composition contains sodium chloride and one or more waste-derived, natural, or animal-derived materials selected from a waste-derived or natural aluminosilicate-containing component selected from sea sand, crushed ceramics, or gemstone scraps, a waste-derived, natural, or animal-derived calcium carbonate-containing component, and a waste-derived, natural, or animal-derived calcium phosphate-containing component.
2. A thermal hand warmer as described in claim 1, which in the case of a two-component system consisting of sodium chloride and a silicate-containing component contains 75 to 90 weight % sodium chloride and 10 to 25 weight % silicate-containing component relative to the total weight of the composition, and in the case of a three- or four-component system consisting of sodium chloride, a calcium carbonate-containing component, and a calcium phosphate-containing component and / or a silicate-containing component contains 70 to 85 weight % sodium chloride, 10 to 18 weight % calcium carbonate-containing component, and 5 to 12 weight % calcium phosphate-containing component and / or silicate-containing component relative to the total weight of the composition.
3. A thermal pocket warmer as described in claim 1 or claim 2, wherein the flame-retardant sheet comprises one or more materials selected from the group consisting of polyarylate cloth, aramid cloth, polyester cloth, felt containing carbonized fibers, carbon cloth, urethane rubber sheet, silicone rubber sheet, composite material of silicone rubber sheet and linen cloth, composite material of silicone rubber sheet and aramid fiber sheet, glass fiber sheet, glass felt, rock wool, refractory ceramic fiber sheet, AES fiber sheet, silica fiber sheet, alumina fiber sheet, and glass wool.
4. A thermal pocket warmer as described in claim 1, wherein the particle diameter of the components derived from waste, natural or animal materials is less than 2 mm.